2017
DOI: 10.3389/fimmu.2017.01630
|View full text |Cite
|
Sign up to set email alerts
|

Potential Effects of Horizontal Gene Exchange in the Human Gut

Abstract: Many essential functions of the human body are dependent on the symbiotic microbiota, which is present at especially high numbers and diversity in the gut. This intricate host–microbe relationship is a result of the long-term coevolution between the two. While the inheritance of mutational changes in the host evolution is almost exclusively vertical, the main mechanism of bacterial evolution is horizontal gene exchange. The gut conditions, with stable temperature, continuous food supply, constant physicochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
141
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(144 citation statements)
references
References 176 publications
(186 reference statements)
2
141
0
1
Order By: Relevance
“…Processed food additive [6,8,9,[11][12][13][14]20] Pathobionts [24][25][26] Probiotics [27,28] Plants [29,30] Vegetables [31] Meat [32,33]…”
Section: Extra-intestinalmentioning
confidence: 99%
See 1 more Smart Citation
“…Processed food additive [6,8,9,[11][12][13][14]20] Pathobionts [24][25][26] Probiotics [27,28] Plants [29,30] Vegetables [31] Meat [32,33]…”
Section: Extra-intestinalmentioning
confidence: 99%
“…The potential pathogenic mechanisms connecting the mTG to CD pathogenesis were summarized recently [7,[12][13][14]25,27,56,58]. The following paragraphs will update and add some additional pathways for the mTG-CD cross-talks.…”
Section: Microbial Transglutaminase Is Potentially Pathogenic To CD Pmentioning
confidence: 99%
“…For example, Helicobacter pylori appears to have been acquired through meat consumption, [93] and novel viral recombinants (SIVcpz) have their origins in bush meat. [95] Even increased consumption and/or domestication of certain plants may have introduced novel microbes and gene variants into the human microbiome. [95] Even increased consumption and/or domestication of certain plants may have introduced novel microbes and gene variants into the human microbiome.…”
Section: Diet Shifts Impact the Human Microbiomementioning
confidence: 99%
“…[94] Domestication of animals may have further intensified microbial transmission as humans and animals became more closely associated. [95] Even increased consumption and/or domestication of certain plants may have introduced novel microbes and gene variants into the human microbiome. A classic example is the presence of a seaweeddegrading microbe in the guts of human populations that ingest high amounts of seaweed.…”
Section: Diet Shifts Impact the Human Microbiomementioning
confidence: 99%
“…It has been reported that use of beta-lactams for treatment of several infections causes development of AmpC beta-lactamase producing E. coli isolates in animal and human intestinal microflora. This casual use also triggers an increase in AmpC beta-lactamase production in Gram-negative pathogens in humans and animals due to the horizontal transfer of resistance genes [8,9] .…”
Section: Introductionmentioning
confidence: 99%